Regions 1.2 and 3.2 of the RNA Polymerase σ Subunit Promote DNA Melting and Attenuate Action of the Antibiotic Lipiarmycin. Issue 2 (29th January 2016) - Morichaud, Zakia; Chaloin, Laurent; Brodolin, Konstantin
Abstract: Initiation of RNA synthesis by bacterial RNA polymerase (RNAP) requires melting of promoter DNA, which is nucleated by the σ subunit during formation of the "open" promoter complex (RPo ). The antibiotic lipiarmycin (Lpm) inhibits promoter melting by blocking access of the template DNA strand to the RNAP active-site cleft. Here we show that Escherichia coli RNAP holoenzymes containing either housekeeping σ 70, with a deletion in the region 3.2, or the stationary phase σ S subunits exhibited hypersensitivity to Lpm and increased cold sensitivity of RPo formation. Similar effects were produced by mutation located ~ 60 Å away from the Lpm binding site within σ 70 region 1.2, controlling − 10 promoter element recognition. Our data suggested that template strand single-stranded DNA competes with Lpm for binding to RNAP and that σ 70 regions 1.2 and 3.2 attenuate Lpm action by promoting DNA duplex opening. Graphical Abstract: Highlights: Promoter DNA opening is a target for genetic regulation and for antibiotics. Regions of the σ 70 factor implicated in DNA opening antagonize the lipiarmycin action. RNAP containing the stationary phase σ S factor displayed hypersensitivity to lipiarmycin. Antibiotic can function as the σ factor selective transcriptional repressor.